(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
In the context of modern medical education, the interdisciplinary integration of clinical sciences is considered a key factor in developing future doctors’ professional competence and clinical thinking. This article explores the didactic, psychological, and technological possibilities for organizing interdisciplinary connections between clinical and fundamental disciplines. The paper focuses on methodological approaches and integrative technologies that enhance teaching efficiency, such as problem-based learning, case-based training, and simulation technologies. Furthermore, it analyzes how integration facilitates cognitive continuity, increases motivation, and promotes the formation of holistic medical knowledge in undergraduate students.